Madison's Metronome : The Constitution, Majority Rule, and the Tempo of American Politics. - Weiner, Greg (University Press of Kansas, 2022)
Examines the significance of time in James Madison's theory of majority rule. Madison worried that the drive for instant political gratification might lead to an inflamed majority that would not rule reasonably. His philosophy-that the natural power of time will defuse passions-is incompatible with the current political ethos that values quick decision-making.